PKM Internasional: Membangun Flourishing Guru Sekolah Indonesia di Luar Negeri melalui Pelatihan Psikologis - Olievia Prabandini Mulyana; Umi Anugerah Izzati; Desi Nurwidawati; Dinda Cahya Novianti; Cherina Safa Wardhani (Politeknik Piksi Ganesha Indonesia, 2025)
This community service program aims to enhance the flourishing or psychological well-being of teachers through psychological training. Teachers face high work-related stress due to the challenges of working in a non-conducive immigrant environment. The intervention included training on self-management, time and energy regulation, assertive communication strategies, reflection, and action planning. The implementation consisted of four weekly sessions using lectures, discussions, simulations, and roleplay. Evaluation results showed an increase in the average flourishing score from 174.4 to 178.5 and a decrease in the number of participants in the very low flourishing category. These findings indicate that the training had a positive impact on teachers’ psychological well-being. This program highlights the importance of targeted psychological support for teachers in high-risk environments and can be replicated in similar contexts.